Internal Locus of Control and Spiritual Intelligence as Drivers of Young Generation’s Financial Behaviour: A Gender Differences Analysis - Aqila Jihan Putri Rahardin; Maulida Nurul Innayah; Wida Purwidianti; Arini Hidayah (Jurnal Maksipreneur, 2026)
Personal financial management behaviour is increasingly vital for Generation Z, who face rapid digitalisation, abundant information, and rising consumerism that influence their financial attitudes and choices. This study investigates the effects of Internal Locus of Control and Spiritual Intelligence on personal financial management behaviour, with gender as a moderating factor, using data from 154 respondents in Banyumas Regency collected through purposive sampling and analysed with PLS-SEM. The findings show that Internal Locus of Control positively and significantly enhances financial management behaviour, indicating that individuals with stronger self-control tend to manage finances more responsibly. Spiritual Intelligence also contributes positively, highlighting the influence of values and awareness on financial decisions. Gender further moderates both relationships, revealing behavioural differences between males and females. Overall, the study underscores the need to integrate psychological and spiritual elements into financial education for Generation Z.